Anti-oxidant and anti-cancer activity of annonamuricata leaf extract in MCF 7 cell line - DR.C.SOWMIA (International Journal of Pharma and Bio Sciences, 2019)
Cancer has been a constant battle globally with a lot of development in cures and preventative therapies. The disease is characterized by cells in the human body continually multiplying with the inability to be controlled or stopped. When the free radicals are balanced by the body’s oxidative defence system, the body is in healthy condition, depletion or loss of antioxidant levels may lead to free radical caused oxidative stress which can cause cellular or tissue damage, DNA damage and cancer. The study is on the Anti-oxidant and Anti-cancer activity of Annonamuricatain MCF 7 cell line. The plant has significant antioxidant activity which is attributed to its high flavonoids content. Therefore A.Muricata is regarded as excellent source for bioactive compounds that can be further developed into a drug to combat oxidative stress. The antioxidant effect against DPPH, Hydroxyl Radical Scavenging Assay, and FRAP which resulted in IC50 values of (80 μl). There is a remarkable anticancer potential observed against cervical cancer cell lines in leaf extract of A.Muricata. There is a maximum cell growth inhibition observed in the concentration at 100μl of methanolic extract. The methanolic extract of A.Muricata showed 58.47% growth inhibition against breast cancer cells